Views of community health workers on the integration of a physiotherapist into a ward-based outreach team - Regina Mashole; Lucy Fernandes; Kebogile Mokwena (AOSIS, 2022)
Background: Due to changes in the disease profile and lifestyle of individuals in South Africa, the limited health care facilities available have experienced congestion and overcrowding, affecting health care service delivery. Ward-based outreach team (WBOT) programmes were implemented to strengthen primary health care, improve access and alleviate the congestion occurring at these facilities. However, WBOTs have limitations in terms of medical knowledge and rehabilitative skills. Objective: To explore the views of community health workers (CHWs) on the integration of physiotherapists into WBOTs. Method: A qualitative research design making use of focus group discussions (FGDs) was used. Through purposive sampling, 58 CHWs who were members of WBOTs were recruited. The WBOTs were from 10 selected primary health care centres in the Tshwane district, Region 2. Six FGDs were conducted. The audio-recorded data were transcribed verbatim. The transcripts were transported into NVivo 12 for thematic analysis. Results: The views of the CHWs were that the WBOTs can benefit from having a physiotherapist as a member of the team. The WBOTs do not have adequate skills to attend to the physiotherapy needs of communities. People in the community have challenges in accessing physiotherapy services, and physiotherapy services can enhance the performance of the WBOTs by providing training to the WBOTs and providing clinical services to community members. Conclusion: Community-based rehabilitative services with a physiotherapist as part of the WBOTs can enhance and strengthen the services of the WBOTs, which can improve the treatment outcomes for communities. Clinical implications: The WBOTS will be empowered to provide clinical services to the vulnerable people in the community that they serve.